Elucidating the progress and impact of ferroptosis in hemorrhagic stroke - Pan, Feixia; Xu, Weize; Ding, Jieying; Wang, Chencen (Frontiers in Cellular Neuroscience, 2023)
Hemorrhagic stroke is a devastating cerebrovascular disease with high morbidity and mortality, for which effective therapies are currently unavailable. Based on different bleeding sites, hemorrhagic stroke can be generally divided into intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH), whose pathogenesis share some similarity. Ferroptosis is a recently defined programmed cell deaths (PCDs), which is a critical supplement to the hypothesis on the mechanism of nervous system injury after hemorrhagic stroke. Ferroptosis is characterized by distinctive morphological changes of mitochondria and iron-dependent accumulation of lipid peroxides. Moreover, scientists have successfully demonstrated the involvement of ferroptosis in animal models of ICH and SAH, indicating that ferroptosis is a promising target for hemorrhagic stroke therapy. However, the studies on ferroptosis still faces a serious of technical and theoretical challenges. This review systematically elaborates the role of ferroptosis in the pathogenesis of hemorrhagic stroke and puts forward some opinions on the dilemma of ferroptosis research.